(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Introduction-Determining the sex of an individual is indeed a crucial step in forensic medicine, as it provides valuable information for various investigative and identification purposes. Teeth are decent source for gender determination. Odontometrics offers a benefit of being simple, speedy, and low cost. Aim- To verify the premolar odontometric differences in sex determination. Methodology- Mesiodistal and buccolingual measurements of premolar crown were calibrated for males and females on 50 pairs of plaster models (25 pairs from both sex) from age group 20-40 years. First and second premolars of Upper and lower jaws of both left and right sides were examined with regard to their mesiodistal (MD) and buccolingual (BL)measurements and the intra-arch premolars linear distance measured from lingual-lingual cusp (3cusp premolars were excluded from study) tips using divider and digital vernier calliper. Result- The Statistical study incorporated the use of SPSS version 23. Significant difference was noted in the odontometric of premolars and lingual-lingual cusp distance. This difference was significant in males. Sexual dimorphism was noted in Mandibular left 1st premolar and maxillary left 2nd premolar with Mesiodistal measurement. The Buccolingual measurements of all the 2nd premolars demonstrated a significant male predominance. Conclusion-It was observed in this study that the use of 2nd premolar buccolingual measurements and linear distance between lingual-lingual cusps of intra arch premolars of opposite side may be used in odontometric as an aid to determine the sex, males showed a significantly higher odontometric.